Theoretical Understandings of Corruption in Iceland: Assessing the Fit of Principal-Agent and Collective Action Theory - Lindsey Mitchell 1993- (2020)
The field of corruption research for much of its existence has had its strongest theoretical underpinnings in principal-agent theory. More and more, authors in this field have begun criticizing principal-agent theory and the lack of effectiveness of anti-corruption policies that are based on said theory, given that they often seem to take a one-size-fits-all approach. Collective action theory, an alternative theory for explaining the causes and persistence of corruption in a state, has been rising in popularity. Neither of these theories have been fully explored in regard to corruption as it exists in Iceland. The purpose of this research is to attempt to establish whether either or both of these theories may be relevant in Iceland, based on core assumptions of each theory. This paper presents findings from an original survey in which data was compiled from members of the Icelandic public who were asked questions related to corruption, and more specifically their willingness to partake in corruption as well as their perception of whether or not others were partaking in corruption. Data indicates that a portion of the public is willing to take part in corruption, challenging the assertion of principal-agent theory that principals are incorruptible. Additional data indicates that individuals widely believe that others would take advantage of opportunities to engage in corruption if given the opportunity, pointing to the possibility that corruption in Iceland may be a collective action problem. Findings are analysed with the state of the developing Icelandic anti-corruption regime in mind in order to highlight potential future ways in which theoretical insights may be taken into account to create a more robust and corruption-resistant system.